Mode and dosage time in polyethylene glycol precipitation process influences protein precipitate size and filterability. (March 2022) - Pons Royo, Maria del Carme; Beulay, Jean-Luc; Valery, Eric; Jungbauer, Alois; Satzer, Peter
Graphical abstract: Highlights: Gradual and stepwise precipitation has several advantages over single PEG addition. Higher purification was achieved by gradual and stepwise precipitation. Improved filterability was achieved by gradual and stepwise precipitation. Addition mode of precipitant influences precipitate characteristics and filterability. Df analysis and FBRM are able predict filterability of precipitates. Abstract: Precipitation has gained interest as alternative to the costly protein A chromatography for monoclonal antibody purification. Traditional precipitation processes are based on direct addition of precipitant in a single dose, with limited control on co-precipitation of impurities and not considering batch-to-batch variations. We propose a gradual dosage of polyethylene glycol to prevent co-precipitation and control resulting floc size. We used focused beam reflectance measurement to demonstrate that the PEG6000 dosage time and the final concentration significantly changes the particle size distribution (PSD). We demonstrated that gradual and stepwise precipitant addition was superior to conventional batch PEG precipitation, improving product yield and purity by a factor of 4 for HCP removal, for samples pre-treated with CaCl2 and caprylic acid. We studied the 3D structure of the precipitates by fractal dimension and showed that precipitates exhibited different compactness and density depending on the dosage time, resulting in different filterability in tangential flow filtration and depth filtration. To switch from batch to continuous PEG addition, the 3D structure of precipitates needs to be considered due to its high impact on the resulting process performance. Focused beam reflectance measurement (FBRM) and fractal dimension can be used to adjust the precipitation methodology to improve the product quality attributes and inform about the design of further purification steps.